Evolution of athletic records: Statistical effects versus real improvements - Gembris, D.; Taylor, J. G.; Suter, D. (Journal of Applied Statistics, 2007)
Athletic records represent the best results in a given discipline, thus improving monotonically with time. As has already been shown, this should not be taken as an indication that the athletes' capabilities keep improving. In other words, a new record is not noteworthy just because it is a new record, instead it is necessary to assess by how much the record has improved. In this paper we derive formulae that can be used to show that athletic records continue to improve with time, even if athletic performance remains constant. We are considering two specific examples, the German championships and the world records in several athletic disciplines. The analysis shows that, for the latter, true improvements occur in 20-50% of the disciplines. The analysis is supplemented by an application of our record estimation approach to the prediction of the maximum body length of humans for a specified size of a population respectively population group from a representative sample. see: http://e3.physik.uni-dortmund.de/~suter/eprints/Statistics_of_records.pdf